Formulating new e-commerce related finance business in indonesian market - Sato, Jun; Ashari Nasution, Reza (The Indonesian Journal of Business Administration, 2016)
Abstract - PT Sinar Mitra Sepadan Finance (the Company hereinafter) is one of JV multifinance company between local Indonesian company and a Japanese multinational company. The company has strong background on IT and is currently pursuing next profit generator. After applying analytical framework of Porter's five forces, BCG matrix and the innovation ambition matrix, the existing businesses of Company is not likely to have prosperous future in the long run. Comparing the rate of growth between existing car finance market and e-commerce market, the Company is suggested to enter into e-commerce finance. In order to create new business in e-commerce market, there are three points to be examined. The first point is how to build up this eco system. The author propose that the Company should have business partnership with payment gateway providers (PGPs) as PGPs have a wide range of connection with e-commerce sites and amount of data. Furthermore, PGPs have a skill of fraud detection. The second point is how to secure the healthiness of receivable of the company. From this perspective, implementation of concept of fintech, utilization of social media for credit approval process, and participation to new credit bureau are suggested. The last point to be examined is how to set up product features in order to generate profit. Based on the nature of e-commerce, small-size, short-term, no collateral finance is considered. Revenue structure of the product is also different from conventional used car finance. There is no charge over customer in e-commerce finance unless becoming overdue. Fee charge over e-commerce sites is the source of income, which is as similar as credit card business. In conclusion, the Company could create new business model in white space of e-commerce with higher growth rate. To enjoy the first mover advantage, its is suggested to start its business implementation which will take approximately 6 months based on the plan by the author.Â Key words: e-commerce, fintech, multifinance